The Diverse Applications of Recombinant BCG-Based Vaccines to Target Infectious Diseases Other Than Tuberculosis: An Overview - Mouhoub, Esma; Domenech, Pilar; Ndao, Momar; Reed, Michael B. (Frontiers in Microbiology, 2021)
Live attenuated Bacillus Calmette-Guérin (BCG) is the world’s most widely used vaccine which is mainly administered for its protection against tuberculosis (TB), particularly in young children. However, since its initial use over 100 years ago, it has also proven to offer a level of protection against various other pathogens, as a consequence of its non-specific immune enhancing effects. Thus, over the past few decades, recombinant BCG (rBCG) technology has been used as a vector to create rBCG vaccines expressing heterologous antigens that elicit immunity against a range of bacterial, viral, and parasitic diseases. Our goal with this mini-review is to provide an up-to date survey of the various techniques, approaches and applications of rBCG-based vaccines for targeting infectious diseases other than TB.